2015
DOI: 10.1016/s2214-109x(15)70085-9
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic expenditure to pay for surgery worldwide: a modelling study

Abstract: Purpose Approximately 150 million individuals face catastrophic expenditure each year from medical costs alone, and many more from the nonmedical costs of accessing care. The proportion of this expenditure arising from surgical conditions is unknown. Because World Bank has proposed eliminating medical impoverishment by 2030, the impact of surgical conditions on financial catastrophe must be quantified so that any financial risk protection mechanisms can appropriately incorporate surgery. Methods To determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
253
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(263 citation statements)
references
References 32 publications
4
253
0
6
Order By: Relevance
“…A modeling study on catastrophic expenditure to pay for surgery worldwide showed that each year, approximately 33 million people worldwide suffer from catastrophic expenditure due to surgical care and almost 3.7 billion people will experience catastrophic payment if they undergo surgery treatments (2). A study by Nguyen et al in Vietnam, on surgical cost and catastrophic expenditure among hospitalized patients with injuries, showed a substantial financial burden of households due to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modeling study on catastrophic expenditure to pay for surgery worldwide showed that each year, approximately 33 million people worldwide suffer from catastrophic expenditure due to surgical care and almost 3.7 billion people will experience catastrophic payment if they undergo surgery treatments (2). A study by Nguyen et al in Vietnam, on surgical cost and catastrophic expenditure among hospitalized patients with injuries, showed a substantial financial burden of households due to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the concept of financial risk protection remains a major focus of many health systems (2,3) and is a core component of universal health coverage (UHC) (1). Financial protection is defined as access to needed and good quality health services without financial catastrophe.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cette diversité rend complexe toute évaluation ou comparaison. • Chaque année, 81 millions de personnes sont confrontées à une ruine financière catastrophique en raison des coûts associés à la chirurgie et à l'anesthésie Pro: Pure service delivery is still needed in global surgery missions 349 et aux coûts non médicaux associés à l'accès aux soins, tels que le transport; 5 • Environ 28-32 % du fardeau mondial de la maladie est attribuable à des maladies traitables grâce à une chirurgie. 6 En outre, au cours des 15 prochaines années, on projette que les besoins pour des services chirurgicaux dans les pays à revenu faible à intermédiaire vont augmenter en raison de l'incidence accrue de cancers, d'accidents de la route, et de maladies cardiovasculaires et métaboliques.…”
Section: Resultsunclassified
“…Access to care is defined as the proportion of the population that can access a facility capable of performing bellwether procedures (cesarean sections, exploratory laparotomy, and treatment of open fractures) (2). The definition was derived by evaluating the four dimensions of access which include timeliness, surgical capacity, safety and affordability (9)(10)(11)(12). It is estimated that nearly 70% of the global population currently cannot access the surgical treatment they need (2).…”
Section: Key Messagesmentioning
confidence: 99%